An Approach to Conformal Transformation Using Symbolic Language Facilities: Application in Electrical Engineering. (16th July 2012) - Nicolaide, Andrei
Abstract : Several studies have been published on this subject concerning especially the calculation of the transformation integral and the plotting of the field spectrum. The method presented in this paper covers larger topics including field strength, circulation, and flux and offers solutions either in closed form or, if not possible, resorting to numerical integration and avoiding, for the considered cases, the utilization of any numerical method like the finite element method. In the present work, the usage of a symbolic language is presented and certain new results have been obtained. The method permits applying the conformal transformation avoiding the hand calculation of integrals for cases in which this calculation is very difficult by traditional procedures because it involves finding some changes of variable suitable for the considered case. For this purpose, the Maple 12 software has been used. An application for electrical engineering which has been considered led the author to find a new solution superior to the known ones.